Stress distribution in CNT-Aluminum matrix composite by changing distances between CNT bundles - Chowdhury, H. T.; Masud, A K M (Journal of Naval Architecture and Marine Engineering, 2016)
Carbon Nanotubes (CNTs) are identified as exceptional in terms of mechanical, electrical, magnetic and optical properties. CNT based composites are also playing a vital role in several fields of science.  In this research, four bundles of CNTs with square Representative Volume Element (RVE) is used and ANSYS Multiphysics 11.0 software is used for simulation purpose. In this study, stress distribution of CNT based Aluminum composite is noticed by changing distances of CNT bundles. Stress distribution and transverse Youngs Modulus are investigated by changing different parameters. From this study it can be known how CNT bundles can be formed together to increase or decrease stress. The brief result is that, if the distance of CNT center from reference point is increased then the stress is decreased.